Randomized clinical trial of stapler hepatectomy versus LigaSure™ transection in elective hepatic resection. Issue 9 (11th July 2018) - Fritzmann, J; Kirchberg, J; Sturm, D; Ulrich, A B; Knebel, P; Mehrabi, A; Büchler, M W; Weitz, J; Reissfelder, C; Rahbari, N N
Abstract: Background: Previous studies have demonstrated stapler hepatectomy and use of various energy devices to be safe alternatives to the clamp-crushing technique in elective hepatic resection. In this randomized trial, the effectiveness and safety of stapler hepatectomy were compared with those of parenchymal transection with the LigaSure™ vessel sealing system. Method: Patients scheduled for elective liver resection at two tertiary-care centres were randomized during surgery to stapler hepatectomy or transection with the LigaSure™ device. Total intraoperative blood loss was the primary efficacy endpoint. Transection time, duration of operation, perioperative complications and length of hospital stay were recorded as secondary endpoints. Results: A total of 138 patients were analysed, 69 in the LigaSure™ and 69 in the stapler hepatectomy group. Baseline characteristics were well balanced between the groups. Mean intraoperative blood loss was significantly higher in the LigaSure™ group than the stapler hepatectomy group: 1101 (95 per cent c.i. 915 to 1287) versus 961 (752 to 1170) ml ( P = 0·028). The parenchymal transection time was significantly shorter in the stapler group ( P = 0·005), as was the total duration of operation ( P = 0·027). Surgical morbidity did not differ between the groups, nor did the grade of complications. Conclusion: Stapler hepatectomy was associated with reduced blood loss and a shorter duration of operation than the LigaSure™ device for parenchymal transection in elective partial hepatectomy. Registration number: NCT01858987 (http://www.clinicaltrials.gov ). Abstract : Reduced blood loss with stapler hepatectomy